Halal certification policies in OIC and non-OIC countries: a comparative analysis of Indonesia, Malaysia, Thailand, and Singapore - Najla, Nailun; Huda, Nurul (Journal of Halal Product and Research (JHPR), 2025)
The rapid growth of the global Muslim population has significantly fuelled the expansion of the halal industry across numerous countries, including those within ASEAN. Halal certification plays a critical role in ensuring products meet Shariah standards, thereby enhancing product safety and appeal for Muslim consumers. This article explores and compares the policies and regulatory frameworks for halal certification in OIC (Organization of Islamic Cooperation) member and non-member countries, specifically Indonesia, Malaysia, Thailand, and Singapore. These countries exhibit fundamental differences in their approaches and implementations: Indonesia relies on the Halal Product Assurance Agency (BPJPH) under the Ministry of Religious Affairs, Malaysia through the Department of Islamic Development Malaysia (JAKIM), Thailand with the support of the Central Islamic Council of Thailand (CICOT), and Singapore through the Islamic Religious Council of Singapore (MUIS). This study identifies the strengths, weaknesses, opportunities, and threats (SWOT) associated with the regulation and implementation of halal certification in these countries. Employing a qualitative approach, data were gathered from scientific literature sources. The findings aim to provide an in-depth understanding of how regulatory frameworks and certification impact the competitive positioning of these nations within the global halal market, supporting their ambitions to emerge as leading global halal hubs.   Keywords: Halal Authority Bodies, Halal Regulations, Halal Certifications, OIC Countries, non-OIC Countries